OP VI – 1 Radiofrequency electromagnetic fields exposure and sleep in adolescents. (18th March 2018) - Cabré, Alba; Vrijheid, Martine; Cardis, Elisabeth; Torrent, Maties; Guxens, Mònica
Abstract : Background/aim: Previous epidemiological studies have assessed the relationship between the use of wireless communication devices, mainly mobile phones, and poor sleep affecting daytime functioning showing inconsistent results. The objective of the study is to assess the association between the use of wireless communication devices and sleep quality and sleep parameters in adolescents of 17.5 years of age. Methods: We used data from a population-based birth cohort established in Menorca in 1997–1998 (n=485), as part of the Spanish INMA –Environment and Childhood– Project. Information about wireless communication devices use was collected using self-reported questionnaires. ActiGraph xGTX3X-BT placed on wrist for seven nights and sleep diaries were used to objectively assess sleep parameters (sleep latency, sleep efficiency, sleep duration, and Wake After Sleep Onset) (n=110). Pittsburgh Sleep Quality Index was used to asses sleep quality (n=226). Logistic and linear regression models adjusted by parental and adolescent socioeconomic and lifestyle variables were used to estimate the association between the use of wireless communication devices and sleep quality and sleep problems. Results: Adolescents that made more than one mobile or cordless phone call per week were more likely to have a worse subjective sleep quality than those making less calls [OR=2.88 (95% CI: 0.93 to 8.97) and OR=2.21 (95% CI: 1.07 to 4.58), respectively]. Adolescents that reported a higher problematic mobile phone use were more likely to have a worse subjective sleep quality than those reporting no problematic use [OR=3.64 (95% CI: 1.32 to 10.02)]. Adolescents that used the tablet 30 min or more daily were more likely to have lower objective sleep efficiency [β=-6.63 (95% CI: −12.49 to −0.77)]. Conclusion: This study suggests that higher mobile phone and cordless phone use, which both represent a higher exposure to RF-EMF to the head, and problematic mobile phone use was associated with poor sleep quality and that higher tablet use decreases sleep efficiency in adolescents.